Epilepsy in KCNH1‐related syndromes. Issue 2 (June 2016) - Mastrangelo, Mario; Scheffer, Ingrid E.; Bramswig, Nuria C.; Nair, Lal. D.V.; Myers, Candace T.; Dentici, Maria Lisa; Korenke, Georg C.; Schoch, Kelly; Campeau, Philippe M.; White, Susan M.; Shashi, Vandana; Kansagra, Sujay; et al.
Abstract: Aim. KCNH1 mutations have been identified in patients with Zimmermann‐Laband syndrome and Temple‐Baraitser syndrome, as well as patients with uncharacterized syndromes with intellectual disability and overlapping features. These syndromes include dysmorphic facial features, nail hypo/aplasia, thumb and skeletal anomalies, intellectual disability, and seizures. We report the epilepsy phenotype in patients with KCNH1 mutations. Methods . Demographic data, electroclinical features, response to antiepileptic drugs, and results of significant diagnostic investigations of nine patients carrying mutations in KCNH1 were obtained from referring centres. Results . Epilepsy was present in 7/9 patients. Both generalized and focal tonic‐clonic seizures were observed. Complete seizure control was achieved with pharmacological treatment in 2/7 patients; polytherapy was required in 4/7 patients. Status epilepticus occurred in 4/7 patients. EEG showed a diffusely slow background in 7/7 patients with epilepsy, with variable epileptiform abnormalities. Cerebral folate deficiency and an increase in urinary hypoxanthine and uridine were observed in one patient. Conclusions . Epilepsy is a key phenotypic feature in most individuals with KCNH1 ‐related syndromes, suggesting a direct role of KCNH1 in epileptogenesis, although the underlying mechanism is not understood.